Dietary Riboflavin Intake and Riboflavin Status in Young Adult Women Living in Metro Vancouver, Canada. Issue 4 (13th March 2021) - Aljaadi, Abeer M; Wiedeman, Alejandra M; Barr, Susan I; Devlin, Angela M; Green, Tim J
ABSTRACT: Background: Nutrition surveys suggest that <10% of Canadian adults have inadequate riboflavin intakes. However, biochemical riboflavin deficiency [erythrocyte glutathione reductase activity coefficient (EGRac) ≥1.40] has been reported in 41% of young adult women living in Metro Vancouver. Canadian Chinese ethnicity comprise >25% of Vancouver's population and are postulated to have poorer riboflavin status than those of European ethnicity because they could be less likely to consume dairy products and fortified wheat. Objectives: The objectives of this study were to determine dietary riboflavin intake and food sources, and to assess the association between riboflavin intake and status in young women of European ( n  = 107) and Chinese ( n  = 91) ethnicities living in Metro Vancouver, Canada. Methods: This was a cross-sectional study conducted in women (aged 19–45 y). Women were healthy, not pregnant or breastfeeding, of European or Chinese ethnicities, and not taking riboflavin-containing supplements for the past 4 mo. Dietary riboflavin intake was assessed using the past-year Diet History Questionnaire II, and riboflavin status (EGRac) was measured in fasting venous blood samples. Results: Only 7% of participants had dietary riboflavin intakes below the Estimated Average Requirement (0.9 mg/d), but 40% of women had biochemical riboflavin deficiency (EGRac ≥1.40). Although more Canadian women of European ethnicity than Chinese ethnicity had biochemical riboflavin deficiency (46% and 34%; P  < 0.001), median dietary riboflavin intake did not differ (1.73 and 1.82 mg/d; P  = 0.587). Dairy products and vegetables contributed the most to riboflavin intake. Energy-adjusted dietary riboflavin intake was inversely associated with EGRac (B = −0.04, 95% CI: −0.07, −0.01). However, after further adjustment the relation was not significant. Conclusions: Overall, women of reproductive age living in Metro Vancouver, Canada, had a low prevalence of inadequate dietary riboflavin intake despite the high prevalence of apparent biochemical riboflavin deficiency. Abstract : Riboflavin from diet met recommended intake, but was not related to blood riboflavin in Canadian women of European and Chinese ethnicities. Dairy products and vegetables were the main dietary sources.